PENDEKATAN NEUROEDUCATION DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF DAN SOSIAL ANAK USIA GOLDEN AGE - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Cendekia Citra Gemilang, 2025)
The purpose of this study was to evaluate the effectiveness of neuroeducation in improving the social and cognitive development of golden age children (0-6 years). Children's limited social interaction with the outside environment and lack of book reading habits were the problems identified. The method used was a survey filled out by mothers of children in the golden age. The results showed that, based on the principles of neuroeducation, the majority of mothers used various stimulation strategies, including cognitive stimulation (3.3), environmental exploration (3.2), and book reading (2.9). However, there was an issue with the lack of habitual book reading, which impacted on the child's language development and memory. The social aspect shows that the mother has provided opportunities for the child to interact with peers (3.4) and taught basic social skills (3.3). However, the child's interaction with the external environment was limited (2.8) and the mother faced difficulties in teaching the child to resolve social conflicts (2.9). As a result, although neuroeducation methods have been used, children need to get the best developmental foundation for their future.